Berat bayi lahir dan kejadian stunting pada anak usia 6-59 bulan di Kecamatan Seberang Ulu I Palembang - Sari, Indah Purnama; Ardillah, Yustini; Rahmiwati, Anita (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Stunting is an indicator of chronic nutritional problem among children under five years old that influenced by nutrition and health status of mothers not only before and during prenancy but also after delivery. One of the long-term effects of stunting is increasing the risk of obesity and other non-communicable diseases. Low birth weight is one of the causes of stunting which also indicates that the fetus has been malnourished during the womb and stunting is a manifestation of malnutrition for a long time. Objectives: This study aimed to determine of the association between low birth weight and stunting, as well as other variables among children between the ages of 6 to 59 months.Methods: This study used cross sectional design. Samples consisted of about 188 eligible children between the ages of 6 to 59 months which selected using simple random sampling technique. Data of the mother’s, infants and environmental characteristics were obtained through face-to-face interviews using a structured questionnaire. Data on birth weight and length were obtained from interviews and crosscheck from the Maternal and Child Health book or child birth records and data on stunting obtained from height Z-score based on age. Data was analyzed using chi-square and logistic regression test.Results: The prevalence of stunting and low birth weight among children between the ages of 6 to 59 months in Seberang Ulu I subdistrict of Palembang was 39.4% and 8.5%, respectively. Birth weight was related to stunting (95% CI=1.28-2.76; p=0.012) and other variables like infectious diseases in the last 1 month (95% CI=1.13-2.26; p=0.009), maternal height (95% CI=1.10-2.19; p=0.016) and household monthly income (95% CI=1.04-2.28; p=0.024). Conclusion: Children with low birth weight had risk of stunting 2.29 higher than children with normal weight after controlling for other factors such as child’s age, mother’s age during delivery, availability of latrine and household monthly income.